2015
DOI: 10.7567/jjap.54.08kd12
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-enhanced chemical-vapor deposition of silicon nitride film for high resistance to potential-induced degradation

Abstract: The antireflection coating (ARC) on crystalline silicon solar cells plays an important role in preventing potential-induced degradation (PID). In a previous work, we reported that the module, which has an ARC prepared by plasma-enhanced chemical-vapor deposition (PE-CVD) using a hollow cathode, indicated high resistance to PID with a constant conventional refractive index (RI). In this work, we report further investigation of the high-PID-resistant ARC. The results indicate that the high-PID resistant ARC had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The chemical compositions of SiN x passivation films affect PID resistance. [ 9,10,71,72,78,79 ] Moreover, thin SiO 2 layers formed underneath the SiN x reduce shunting‐type PID. [ 80–82 ] Surface morphology also affects PID.…”
Section: Pid Phenomena In Conventional P‐type C‐si Pv Cell Modulesmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical compositions of SiN x passivation films affect PID resistance. [ 9,10,71,72,78,79 ] Moreover, thin SiO 2 layers formed underneath the SiN x reduce shunting‐type PID. [ 80–82 ] Surface morphology also affects PID.…”
Section: Pid Phenomena In Conventional P‐type C‐si Pv Cell Modulesmentioning
confidence: 99%
“…In addition, it is preferable to have intrinsically PID‐free solar cells that are independent of module manufacturers or installers to apply the right (expensive) materials or correct grounding on the systems. Actually, PID has been shown to be preventable by chemical composition modification of the SiN x passivation layers on the emitter side of c‐Si PV cells [ 9,10,71,72,78,79 ] because the increased conductivity of the SiN x layer reduces the voltage across the SiN x layer. Chemical composition modification is realized merely by changing the ratio of silane (SiH 4 ) gas flow rate to the ammonia (NH 3 ) gas flow rate during chemical vapor deposition (CVD).…”
Section: Pid Phenomena In Conventional P‐type C‐si Pv Cell Modulesmentioning
confidence: 99%
“…With this module, only the light-receiving side of the solar cell, i.e. the anti-reflection coating, which is more important for generating the PID phenomena, 3,12,[22][23][24][25][26][27][28][29][30] is encapsulated during the PV module fabrication. The single-encapsulation module can be analyzed directly after PID testing because the nonlight-receiving side of the module is in the air and because no pre-processing is required for micro-analyses of the PID phenomena of the whole cell.…”
Section: Introductionmentioning
confidence: 99%
“…V. Naumann et al think that PID is related with sodium decorated stacking faults across the pn junction under high system voltage [15][16][17][18]. S. Koch, K. Mishina and Zhou found that adding two or three layers coatings into crystalline silicon solar cells could reduce the sensitivity of PID [19][20][21]. J. Hylsky et al deem that crystalline silicon solar cells with the phosphorus silicate glass show properties resistive against PID [22].…”
Section: Introductionmentioning
confidence: 99%